Setting in psicoterapia: riflessioni sul setting in video-presenza - De Lisi, Donatella; Ritacco, Ilario (Il sogno della farfalla, 2021)
During the lockdown caused by COVID-19, online psychotherapy represented the only valuable alternative to the interruption, until a date to be determined, of the psychotherapeutic treatment. Many psychotherapists decided to carry on with video conference sessions: in this new context the patient and the psychotherapist are able to meet through a device which allows them to see and feel each other even if physically distant. In order to work online, the minimum prerequisites were: to have a good internet connection, to download a programme to be able to make video calls, to have a private space where privacy was guaranteed together with the respect of the session’s time . The author reflects on the idea that setting is based on a non conscious rapport between the doctor and the patient. Therefore, changes or potential changes in the setting should not represent a threat but rather be naturally accepted, particularly during the extreme circumstances determined by the pandemic. The author finally concludes how the adjustments applied to the setting have not represented a dramatic upheaval. Indeed, the therapeutic treatment has not been radically altered since it has been supported by the same theoretical and methodological architecture and by the same intention to cure.